Russian Federation : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This Selected Issues paper analyzes the entrenched inflation in Russia. It presents a possible explanation for the entrenched inflation stating that the Russian economy is facing increasing supply-side constraints in goods and labor markets. The paper focuses on measuring the performance of fiscal policy in Russia. It examines capital structures and vulnerabilities for the corporate sector in Russia. Recent developments and remaining challenges for the Russian banking sector are analyzed. Terms of trade and economic growth in the Former Soviet Union are also discussed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Macroeconomics